PENERAPAN PENDEKATAN KETERAMPILAN PROSES UNTUK MENINGKATKAN KETERAMPILAN MENULIS LAPORAN PENGAMATAN SISWA KELAS V SD NEGERI 22 SEI PAKNING KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Tati Harnis; otang Kurniaman; zariul antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problems that occurred in the fifth grade students of SD Negeri 22 Sei Pakning Bukit Batu subdistrict Bengkalis is low learning achievement students in writing a report on the first half. Some of the factors that lead students to master a difficult subject to write reports include students and teachers from less than the maximum in the use of instructional media other causes originate and students who are still a lot of play in the learning process. This research aims to improve student learning outcomes Indonesian. Results of this study was obtained from observations of the activities of teachers and students during the learning process and student achievement test. This research is a form of action research consisted of two cycles. An increase in activity of teachers and students at each cycle using the application process skills approach. In the first cycle replicates the average value replications 61.05, students who completed as many as 5 people (26.32.%), And incomplete 14 people (73.68%). While in the second cycle the average value rose by 12.63 points to 75.58 with completeness 19 students (100%), and students who do not complete 0 (0%). From the results of this study concluded that the application process skills approach can improve learning outcomes Indonesian Elementary School fifth grade students 22 Sei Pakning Bukit Batu subdistrict BengkalisKeywords: Application Process Skills Approach,